Ультраструктура Neoperezia chironomi (Microspora, Thelohaniidae), найденных в личинках Chironomus plumosus из Польши - Wita, I.; Ovcharenko, M.O.; Dzieszuk, U. (Вестник зоологии, 1998)
The microsporidium Neoperezia chironomi Issi and Voronin, 1979 a parasite of larvae of Chironomus plumosus L., is described based on ultrastructural characteristics. The earliest stages observed were diplokaryotic meronts. Sporogony is disporoblastic. The uninucleate sporoblasts and spores are enclosed in a sporophorous vesicle. Fixed and stained spores measure 4.0 (3.8—4.2) * 2.5 (2.3—2.8) μm. The polaroplast is lamellar. The polar filament is isofilar with 24-28 coils, arranged in 2-4 layers. The material from Poland is compared to the original description of N. chironomi.